2018
DOI: 10.1589/jpts.30.1150
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hindlimb unloading and reloading on the soleus and plantaris muscles in diabetic rats

Abstract: [Purpose] This study aimed to induce disuse muscle atrophy in Goto-Kakizaki rats, a type 2 diabetes model, to investigate the effects of reloading on the soleus and plantaris muscles. [Materials and Methods] Wistar and Goto-Kakizaki (GK) rats were divided into 6 groups: Wistar Control (WC), GK Control (GC), Wistar Tail suspension (WS), GK Tail suspension (GS), and Wistar Reload (WR), GK Reload (GR). [Results] Investigation of myofiber cross-sectional area in Goto-Kakizaki rat soleus muscles indicated that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…Notably, the first few days of the experimental period, rats in the simulated gravity groups all exhibited a transient decrease in body weight, which subsequently plateaued and then increased. This pattern has been observed in other ground-based models, as well as astronauts (Matsumoto et al, 2011;Stein 2012;Madokoro et al, 2018) (Figure 2C). During the experiment, the body weights of rats in both the control and sham groups significantly increased from baseline.…”
Section: Discussionsupporting
confidence: 80%
“…Notably, the first few days of the experimental period, rats in the simulated gravity groups all exhibited a transient decrease in body weight, which subsequently plateaued and then increased. This pattern has been observed in other ground-based models, as well as astronauts (Matsumoto et al, 2011;Stein 2012;Madokoro et al, 2018) (Figure 2C). During the experiment, the body weights of rats in both the control and sham groups significantly increased from baseline.…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies reported that two-week tail suspension caused Gas muscle atrophy in rodents [ 18 21 ], and subsequent two-week reloading caused recovery of the Gas muscle wet weight in young adult mice [ 21 ] and rats [ 19 ]. In addition, a previous study of unloaded T2DM rats followed by a week of reloading revealed no marked difference in the course of soleus muscle mass loss and recovery [ 22 ]. Therefore, the results were consistent with those studies, indicating that muscle atrophy was caused by tail suspension.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cause of muscle loss at R1w in T2DM remains speculative, but given the high fasting blood glucose level at R1w, it may have been caused by insulin resistance or increased inflammation due to reloading. However, the level of muscle damage after reloading was not shown to differ markedly between non-DM and T2DM rats [ 22 ], and the anabolic response to diet was similar in T2DM subjects and age-matched controls [ 26 ]. Therefore, the findings were similar to previous results, suggesting that the muscle protein metabolism did not differ markedly due to activity-dependent changes between non-DM and T2DM rats.…”
Section: Discussionmentioning
confidence: 99%